A SiPM-based isotropic-3D PET detector X'tal cube with a three-dimensional array of 1 mm(3) crystals - Yamaya, Taiga; Mitsuhashi, Takayuki; Matsumoto, Takahiro; Inadama, Naoko; Nishikido, Fumihiko; Yoshida, Eiji; Murayama, Hideo; Kawai, Hideyuki; Suga, Mikio; Watanabe, Mitsuo (Physics in medicine & biology, 2011)
We are developing a novel, general purpose isotropic-3D PET detector X'tal cube which has high spatial resolution in all three dimensions. The research challenge for this detector is implementing effective detection of scintillation photons by covering six faces of a segmented crystal block with silicon photomultipliers (SiPMs). In this paper, we developed the second prototype of the X'tal cube for a proof-of-concept. We aimed at realizing an ultimate detector with 1.0 mm(3) cubic crystals, in contrast to our previous development using 3.0 mm(3) cubic crystals. The crystal block was composed of a 16 × 16 × 16 array of lutetium gadolinium oxyorthosilicate (LGSO) crystals 0.993 × 0.993 × 0.993 mm(3) in size. The crystals were optically glued together without inserting any reflector inside and 96 multi-pixel photon counters (MPPCs, S10931-50P, i.e. six faces each with a 4 × 4 array of MPPCs), each having a sensitive area of 3.0 × 3.0 mm(2), were optically coupled to the surfaces of the crystal block. Almost all 4096 crystals were identified through Anger-type calculation due to the finely adjusted reflector sheets inserted between the crystal block and light guides. The reflector sheets, which formed a belt of 0.5 mm width, were placed to cover half of the crystals of the second rows from the edges in order to improve identification performance of the crystals near the edges. Energy resolution of 12.7% was obtained at 511 keV with almost uniform light output for all crystal segments thanks to the effective detection of the scintillation photons.